Electromagnetic modelling of rf mems structures - Edward, David Miieg. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Radio Frequency Micro - Electro - Mechanical System (RF MEMS) is one of the emerging applications in MEMS technology which are used in phase - shifters, couplers, filters, tunes or antennas. In order to model and optimize the performance of the devices, an accurate knowledge and understanding of the electrom agnetic field such as the Maxwell theorem is essential. In this project, a new numerical method is introduced to analyze the problems which cause the limitation of the conventional time domain technique. The method is expanded to analyze MEMS devi ces with moving parts with the Finite Different Time Domain (FDTD) method for Electromagnetic (EM) field. By employing transformation in the time factor, the grid generation technique can be applied to the time - domain analysis of a moving object. These tec hniques are implemented in analyzing structure of uninformed shape and motion. The s imulation method for the RF MEMS variable capacitor is applied to the analysis of a two - dimensional (2D) Transverse Electric (TE) mode. The acceleration of the p lates is derived from the equilibrium between the spring force and the electrical force. A damping constant is added into the system and the motion of the MEMS variab le capacitor is analyzed. The s imulation will analyze the damping effect towards the motio n due to the damping mechanism such as fluids damping and electronics damping.